AnDHN, a Dehydrin Protein From Ammopiptanthus nanus, Mitigates the Negative Effects of Drought Stress in Plants - Sun, Yibo; Liu, Linghao; Sun, Shaokun; Han, Wangzhen; Irfan, Muhammad; Zhang, Xiaojia; Zhang, Li; Chen, Lijing (Frontiers in Plant Science, 2021)
Dehydrins (DHNs) play crucial roles in a broad spectrum of abiotic stresses in model plants. However, the evolutionary role of DHNs has not been explored and the function of DHN proteins is largely unknown in Ammopiptanthus nanus, an ancient and endangered legume species from the deserts of northwestern China. In this study, we isolated a drought-response gene (c195333_g1_i1) from a drought-induced RNA-seq library of A. nanus. Evolutionary bioinformatics showed that c195333_g1_i1 is an ortholog of Arabidopsis DHN, and we renamed it AnDHN. Moreover, DHN proteins may define a class of proteins that are evolutionarily conserved in all angiosperms that has experienced a contraction during the evolution of legumes. Arabidopsis plants overexpressing AnDHN exhibited morpho-physiological changes, including an increased germination rate, higher relative water content, higher proline content, increased POD and CAT activities, and lower contents of malondialdehyde (MDA), H2O2 and O2-, and longer root length. Our results showed that the transgenic lines had improved drought resistance with deep root system architecture, excellent water retention, increased osmotic adjustment, and enhanced ROS scavenging. Furthermore, the transgenic lines also had enhanced salt and cold tolerance. Our findings demonstrate that AnDHN may be a good candidate gene for improving abiotic stress tolerance in crops.